Implementasi Sistem IoT untuk Pemakaian Air dan Sistem Pembayaran PAMSIMAS Sawojajar - Sabina Sabina; M. Abu Jihad Plaza R (Fakultas Teknik Universitas Muhammadiyah Parepare, 2026)
Clean water management under the PAMSIMAS program in Sawojajar Village currently faces efficiency challenges due to the manual meter recording system and conventional payment mechanisms. The main obstacles identified include inaccurate water consumption data due to human error and low customer compliance in paying fees, which impacts operational costs for pump maintenance. This research aims to implement an Internet of Things (IoT)-based system as an automated solution for monitoring and controlling water distribution. This system was developed using the Waterfall method, involving two user roles: the admin and the customer. The system is able to record usage in real time and automatically cut off water flow if the customer is late in making monthly payments. Water flow will be reactivated instantly after the system verifies the customer's online payment. The results of this implementation are expected to increase transparency in water usage data, facilitate payment access for the community, and ensure cash stability for managers through a firm and automated control system. This digitalization is transforming into a strategic step in modernizing more effective and accountable rural water resource governance.